Manajemen Pendapatan dan Krisis Keuangan di Malaysia - Yuskar, .; Taib, Fauziah Md.; Ibrahim, Daing Nasir (Fakutas Ekonomi Unika Widya Mandala Surabaya, 2004)
This study examines evidence on earnings management in Malaysia. During the financial crisis in Asia since mid of 1997, including Malaysia, many Malaysian companies experienced financial problems and loss until the financial reporting period of 1998. In this situation, it is assumed that Malaysia companies were motivated to apply earnings management in the period of t998 by